2023
DOI: 10.1536/ihj.22-435
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of Chinese Patients with Premature Acute Coronary Syndrome

Abstract: This study aimed to investigate the clinical characteristics and major adverse cardiovascular events (MACEs) of Chinese patients with premature acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI). This study was a secondary retrospective analysis involving 2114 ACS patients undergoing PCI at a single center in China. The patients were divided into two groups according to age (premature ACS group: !55 years in men, !65 years in women; nonpremature ACS group: > 55 years in men, > 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…These data are consistent with our results. However, numerous studies suggested that women are more likely than men to develop side effects after PCI, regardless of age, and young women have a higher mortality risk after an elective PCI 22–24 . Although sex differences were significant in univariate analysis, it was not an independent risk predictor for long‐term mortality.…”
Section: Discussionmentioning
confidence: 91%
“…These data are consistent with our results. However, numerous studies suggested that women are more likely than men to develop side effects after PCI, regardless of age, and young women have a higher mortality risk after an elective PCI 22–24 . Although sex differences were significant in univariate analysis, it was not an independent risk predictor for long‐term mortality.…”
Section: Discussionmentioning
confidence: 91%
“…These time intervals were chosen because all the required atmospheric data were available and collected on a retrospective basis. We defined premature ACS as coronary disease diagnosed before 55 years of age [5]. Patients with one of two forms of ACS, either ST-elevation myocardial infarction (STEMI) or non-ST-elevation ACS (NSTE-ACS), were included in this study.…”
Section: Study Populationmentioning
confidence: 99%
“…Based on the age at disease onset, ACS is considered premature when it develops in young individuals (<55 years of age), similar to the definition of premature coronary artery disease [5]. The manifestation of ACS in young subjects is associated with an important decrease in life expectancy [5].…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies had also adopted the same age criteria. 11 , 12 RIFLE (risk, injury, failure, loss, end stage renal disease), AKIN (acute kidney injury network), and KDIGO (kidney disease: improving global outcomes) are considered favorable tools for diagnosing AKI. However, the KDIGO criteria have been recognized to better correlate disease severity with cardiovascular and other complications.…”
Section: Introductionmentioning
confidence: 99%